PENERAPAN STRATEGI GNT DENGAN MEDIA GAMBAR DALAM PENINGKATAN HASIL BELAJAR IPS TENTANG AKTIVITAS EKONOMI DI KELAS IV SD - yunianti, sri (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Implementation of Guided Note Taking (GNT) Strategy Using Pictures Media in Improving Social Science Learning for the Fourth Grade Students of Elementary Schools. The objectives of this research are: (1) to improve social science learning about economic activities, (2) to describe the steps on the implementation of GNT strategy using pictures media. This research is a collaborative Classroom Action Research (CAR). Validity of data in this research was analyzed using triangulation of sources and techniques. Data were analyzed using quantitative and qualitative analysis consisting of data reduction, data display, and drawing conclusion or verification. The results of this research showed that: (1) the implementation of GNT strategy using pictures media can improve social science learning about economic activities, (2) the implementation of GNT strategy using pictures media conducted through stages as follows: (a) the distribution of worksheet; (b) the distribution of images of economic activities; (c) delivery of materials and guidance to complete worksheet with question and answer; (d) reading the results of worksheets together; and (e) clarification of the question and answer. Keywords: GNT strategy, pictures media, learning outcomes, social science Abstrak: Penerapan Strategi GNT dengan Media Gambar dalam Peningkatan Hasil Belajar IPS di Kelas IV SD. Tujuan penelitian ini yaitu (1) meningkatkan hasil belajar IPS tentang aktivitas ekonomi; (2) mendeskripsikan langkah-langkah penerapan strategi GNT dengan media gambar. Penelitian ini menggunakan penelitian tindakan kelas kolaboratif. Validasi data menggunakan triangulasi sumber dan teknik. Analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1) penerapan strategi GNT dengan media gambar dapat meningkatkan hasil belajar siswa; (2) penerapan strategi GNT dengan media gambar dilakukan dengan langkah-langkah: (a) pembagian lembar catatan secara estafet; (b) pembagian gambar aktivitas ekonomi dengan estafet; (c) penyampaian materi dan pembimbingan mengisi lembar catatan dengan tanya jawab; (d) pembacaan hasil catatan bersama-sama; dan (e) klarifikasi dengan tanya jawab. Kata Kunci: strategi GNT, media gambar, hasil belajar, IPS